Effects of dietary astaxanthin, ractopamine HCl, and gender on the growth, carcass, and pork quality characteristics of finishing pigs - J R Bergstrom; Terry A Houser; Michael D Tokach; Steven S Dritz; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 144 finishing pigs (initially 226 lb) were used to evaluate the effects of various levels and sources of added dietary astaxanthin (AX: 0, 2.5, 5, 7.5, and 10 ppm), as well as ractopamine HCl (Paylean), on growth, carcass, and pork quality characteristics of barrows and gilts. Pigs were blocked by gender and weight and randomly allotted to 1 of 9 dietary treatments fed for approximately 26 d pre-harvest. Dietary treatments consisted of a corn-soybean meal-based control, the control with 5, 7.5, or 10 ppm AX from Phaffia rhodozyma yeast, the control with 5 ppm synthetic AX, and the control with 9 g/ton Paylean and 0, 2.5, 5, and 7.5 ppm AX from Phaffia rhodozyma yeast. There were 2 pigs per pen and 8 pens per treatment (4 pens per treatment x gender combination). Overall, barrows had greater (P<0.01) ADG and ADFI than gilts, while ADG and final BW increased (P<0.01) and F/G improved for pigs fed Paylean. For carcass characteristics, barrows had greater (P<0.01) backfat depth and less (P<0.01) longissimus muscle area and fat-free lean than gilts. Pigs fed Paylean had greater (P<0.01) HCW, yield, and longissimus muscle area than those that received non-Paylean treatments. Growth performance and carcass characteristics of pigs fed AX were not different than control pigs. Although there were no differences in the initial subjective color scores, the discoloration scores of longissimus chops increased (linear, P<0.01) daily during 7 d of retail display, and were greater (P<0.01) for barrow chops on d 7 compared to gilt chops (gender x day interaction, P<0.01). Also, the overall average discoloration scores and change in d 0 to 3 objective total color were lower (P<0.01) for gilts and pigs fed Paylean, although the difference between gilts and barrows was smaller when they were fed Paylean (gender x treatment interaction, P<0.01). Modest differences in measures of pork color during retail display were associated with added dietary AX, but these did not result in an increase in color shelf-life or reduction in the objective measure of total color change. Collectively, these observations indicated a greater (P<0.01) color shelf-life for chops from gilts and pigs fed Paylean.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Astaxanthin; Carcass characteristics; Pork color